Analisis Jalur Faktor Angka Kematian Ibu di Provinsi Jawa Timur Tahun 2014 - Abdi Iswahyudi Yasril; Mahmudah Mahmudah (Universitas Airlangga, 2018)
Path analysis was a statistical analysis technique which was developed from multiple regression analysis. This method was used to analyze the causal relationship that involve many variables such as maternal mortality rate (MMR). Many variables influenced the MMR but it was not easy to find the dominant variable because it will create problems multicolinearity. Therefore it used path analysis to analyze the direct and indirect effects in the incidence of MMR based on the model of causal relationship.The purpose of this study to apply path analysis on factors that affect maternal mortality rate in East Java province. This study was a non-reactive using data SUSENAS and East Java Provincial Health Profile 2014 on maternal mortality rate in all districts in East Java using path analysis. The results of path analysis showed that there was influence between the variables of women who married at age <17 years (p = 0.045; β = 0.376), birth attendance by non-medical (p = 0.013; β = 0.475) and obstetric complications (p = 0.036; β = 0.323) on the incidence of MMR. Analyzed furthermore of variables woman who married at age <17 years (β = 0.528) and birth attendance by non-medical (β = 0.632) influenced directly and indirectly to MMR. It was expected by using this path analysis health practitioners could improve their services and assistances to all pregnant women for early detection of high risk pregnancy.